Development of Character Education in Madrasas And Pesantren - Adah Aliyah; Enoh Enoh; Aan Hasanah; Bambang Samsul Arifin (Edumaspul: Jurnal Pendidikan, 2023)
The aim of this article is to examine the development of character education in madrasas and Islamic boarding schools. The research approach employed is qualitative with a literature study method (library research). The data collection technique involves searching for sources and reconstructing information from various sources such as books, journals, and existing research. Content analysis is used as the method of analysis. The development of character education in madrasas and Islamic boarding schools involves a holistic and integrated approach, with a focus on habits, learning, and daily interactions. The necessary steps include creating a supportive environment, developing a character-based curriculum, improving the quality of teachers, and organizing character-based extracurricular activities. The challenge in this development lies in adapting to social and technological changes in the 5.0 era. In this era, it is important to integrate traditional values with relevant values in the digital context and to utilize technology ethically.